The Implementation of Total Quality Management at Alkhairaat Islamic Boarding School Kalumpang Ternate - Limatahu, Kartini; Arief, Armai; Priharta, Andry (Technium Social Sciences Journal, 2022)
This study is intended to describe or analyze the implementation of Total Quality Management (TQM) at Alkhairaat Islamic Boarding School Kalumpang Ternate, in addition to finding the implementation of Total Quality Management at Alkhairaat Islamic Boarding School Kalumpang, Ternate has been following the planning to achieve quality targets. Therefore, the method used is qualitative-descriptive through the sociological-historical approach. In this study, data acquisition was carried out through observation, interviews, documentation, and a search for literature studies of references related to the object of research. The findings showed that Alkhairaat Islamic Boarding School Kalumpang Ternate students do not stay/live in the dormitory. Furthermore, Alkhairaat Islamic Boarding School Kalumpang Ternate uses the pattern of Islamic Boarding School, but the system and mechanism do not use Islamic Boarding School. Islamic Boarding School is identical with kiyai as the head, but the existence of Alkhairaat Islamic Boarding School Kalumpang Ternate head or ustad (as the people of North Maluku call it) is not visible. Accordingly, in the implementation of Total Quality Management in Alkhairaat Islamic Boarding School Kalumpang Ternate, there are four components for quality improvement, there are organizing process quality based boarding school education, organizing service quality based boarding school education, organizing environmental quality based boarding school education, and organizing Human Resources (HR) quality based boarding school education. Quality improvement of each component has its plan, control, and improvement process. The education at Alkhairaat Islamic Boarding School Kalumpang Ternate in its application is following planning based on Total Quality Management (TQM) and in its implementation continuous improvement is carried out.